2018
DOI: 10.1029/2018gl078591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Confining Stress on the Semipermeability of Siliceous Mudstones: Implications for Identifying Geologic Membrane Behaviors of Argillaceous Formations

Abstract: The semipermeability arising from filtration effects on ionic species at the pore spaces in clay minerals has been recognized as a fundamental transport property of argillites. However, little is known about the dependence of the semipermeability on the confining stress that controls the pore sizes. Thus, we investigated the evolution of the semipermeability during cyclic loading by performing chemical osmosis experiments on siliceous mudstones. Results show that the semipermeability irreversibly increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…With each subsequent cycle it does not recover to the initial values and this phenomenon is also known as a permeability hysteresis [ [1] , [2] , [3] , [4] , [5] , [6] ]. According to the classical poromechanics theory, the apparent permeability degradation and hysteresis occur as a result of mechanical compaction by plastic deformations, and microcracks closure [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ] which agrees well with rock mechanics [ [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ]. In addition, during compaction, crushing of mineral grains can occur within the rocks as a result of which a certain amount of detrital material can form [ 56 ] with a size from a few microns (colloids) to tens of microns (fines) which is especially typical for higher loads.…”
Section: Introductionmentioning
confidence: 99%
“…With each subsequent cycle it does not recover to the initial values and this phenomenon is also known as a permeability hysteresis [ [1] , [2] , [3] , [4] , [5] , [6] ]. According to the classical poromechanics theory, the apparent permeability degradation and hysteresis occur as a result of mechanical compaction by plastic deformations, and microcracks closure [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ] which agrees well with rock mechanics [ [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ]. In addition, during compaction, crushing of mineral grains can occur within the rocks as a result of which a certain amount of detrital material can form [ 56 ] with a size from a few microns (colloids) to tens of microns (fines) which is especially typical for higher loads.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wang et al [ 10 ] analyzed how the confining pressure and unloading rate impacted crack propagation; the results indicated that under greater confining pressure, crack formation post-failure, and the rate of crack expansion, increased with higher unloading rates. Takeda et al [ 11 ] examined the semi-permeability evolution of Wakkanai mudstones during cyclic loading and unloading, emphasizing the importance of considering the applied stresses when estimating argillite semi-permeability. In response to stress evolution induced by activities such as excavation and mining, Zhang et al [ 12 ] executed a multi-level axial stress triaxial unloading test that defined the alteration law of mechanical parameters (friction, cohesion, and dilatancy angle) using an unloading factor representing rock specimen damage mechanisms.…”
Section: Introductionmentioning
confidence: 99%